Development of polyvinyl alcohol nanofiber scaffolds loaded with flaxseed extract for bone regeneration: phytochemicals, cell proliferation, adhesion, and osteogenic gene expression - Abdelaziz, Ahmed G.; Nageh, Hassan; Abdalla, Mohga S.; Abdo, Sara M.; Amer, Asmaa A.; Loutfy, Samah A.; Abdel Fattah, Nasra F.; Alsalme, Ali; Cornu, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Chemistry, 2024)
This study assessed the incorporation of a flaxseed extract into electrospun polyvinyl alcohol (PVA) nanofibers to produce nanofiber scaffolds for bone tissue engineering. High-performance liquid chromatography analysis of the total flaxseed extract revealed the presence of ten compounds, including polyphenolic acids and flavonoids. The diameter of the resulting nanofibrous structures ranged from 252 nm for pure PVA nanofibers to 435 nm for PVA nanofibers loaded with 30 wt.% flaxseed extract (P70/E30). Their function as scaffolds was evaluated in MG-63 osteoblast cultures. The optimization of key nanofiber characteristics (diameter, extract concentration, hydrophilicity, swelling behaviour, and hydrolytic degradation) enhanced the scaffold's efficacy in supporting cell adhesion, proliferation, and differentiation.Flaxseed extract-loaded nanofibers promoted cell proliferation/viability (MTT assay) compared with pure PVA nanofibers: cell viability was 74.5% for PVA nanofibers and 102.6% for P70/E30 nanofibers (1 mg/mL for both). However, flaxseed extract incorporation reduced cell adhesion (206 cells/section for PVA nanofibers vs 151 for P70/E30 nanofibers) due to the scaffold hydrophilicity decrease after extract loading. Importantly, the nanofibrous scaffolds induced MG-63 osteoblast differentiation, as indicated by the significant upregulation of osteogenic genes (RT-qPCR analysis): 1.2-fold and 106.8-fold for RUNX2, 1.6-fold and 25.9-fold for COL1A1, and 2.4fold and 16-fold for OCN with PVA and P70/E30 nanofibers, respectively, compared to control without scaffolds. The tailored optimization of the nanofibrous scaffold properties holds promise for regenerative medicine applications.